THE IMPLEMENTATION OF WRITE-PAIR-SHARE TECHNIQUE IN TEACHING WRITING RECOUNT TEXT TO THE EIGHTH GRADE STUDENTS OF SMPN 1 TARIK (RETAIN, 2013)
Penelitian ini bertujuan untuk mendeskipsikan penerapan teknik Write-Pair-Share untuk mengajar menulis teks recount pada siswa kelas delapan di SMPN 1 Tarik, untuk mendeskripsikan respon siswa terhadap penerapan teknik Write-Pair-Share untuk mengajar menulis teks recount, dan untuk mendeskripsikan hasil menulis teks recount siswa setelah penerapan teknik Write-Pair-Share untuk mengajar menulis teks recount. Penelitian ini menggunakan penelitian deskriptif qualitative tanpa ada perhitungan statistik. Hasil penelitian ini menunjukkan bahwa teknik Write-Pair-Share sukses diterapkan di kelas dan teknik yang membantu baik guru dan siswa dalam proses belajar mengajar menulis teks recount dalam konteks ‘knowledge of content, organization, vocabulary, language use, and mechanics’. Teknik Write-Pair-Share mampu mengajak minat siswa untuk menulis. Kata Kunci: Menulis, teknik Write-Pair-Share, teks recount, siswa kelas delapan, respon siswa. Abstract This study is conducted to describe the implementation of Write-Pair-Share technique in teaching writing recount text to the eighth grade students of SMPN 1 Tarik, the students’ responses toward the implementation of Write-Pair-Share technique in teaching writing recount text, and the students result after the implementation of Write-Pair-Share technique in teaching writing recount text. This study used descriptive qualitative research without any statistical calculation. The result of this study showed that Write-Pair-Share technique was successfully implemented in class and it was helpful technique for both the teacher and the students in teaching and learning process of writing recount text in terms of ‘knowledge of content, organization, vocabulary, language use, and mechanics’. Write-Pair-Share technique could engage the students’ willingness to write. Keywords: Writing, Write-Pair-Share technique, recount text, eighth grade students, students’ response.